2011
DOI: 10.3109/08977194.2011.599324
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin (GDF-8) inhibits chondrogenesis and chondrocyte proliferationin vitroby suppressing Sox-9 expression

Abstract: Here, we investigate a possible direct role for myostatin in chondrogenesis. First, we examined the effects of myostatin on the proliferation of bone marrow stromal cells (BMSCs) and epiphyseal growth plate (EGP) chondrocytes isolated from myostatin-deficient mice. Results show that myostatin deficiency is associated with a significant (P<.001) increase in proliferation of both BMSCs (+25%) and EGP chondrocytes (+35%) compared to wild-type cells. Next, we examined the effects of myostatin treatment on chondrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 45 publications
4
24
1
Order By: Relevance
“…In addition, the proliferation rate of chondrocytes isolated from the epiphyseal growth plates of mstn Ϫ/Ϫ mice is greater than that of cells from WT mice (79). Notwithstanding, our study failed to detect significant differences in the number of bone LRCs in WT and mstn Ϫ/Ϫ mice, regardless of region.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, the proliferation rate of chondrocytes isolated from the epiphyseal growth plates of mstn Ϫ/Ϫ mice is greater than that of cells from WT mice (79). Notwithstanding, our study failed to detect significant differences in the number of bone LRCs in WT and mstn Ϫ/Ϫ mice, regardless of region.…”
Section: Discussioncontrasting
confidence: 74%
“…However, bone marrow-derived MSCs obtained from myostatinnull mice exhibited increased osteogenic differentiation compared with cells from wild-type mice (13), and myostatin expression increased transiently after fracture (47). Myostatin treatment reduced type II collagen synthesis and expression of Sox9 mRNA, a transcription factor for chondrocyte differentiation (48). Thus, it is tempting to speculate that myostatin may promote the differentiation of MSC or MSC-derived cells into osteoblastic cells, an important step in the initiation of AAC.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work in our lab showed that myostatin can inhibit the proliferation of aged bone marrow stromal cells (Bowser et al, 2013), that bone marrow stromal cells from mice lacking myostatin show increased proliferation (Elkasrawy et al, 2011), and that myostatin can inhibit chondrogenesis in vivo and in vitro (Elksrawy et al, 2012). These data may at least in part explain the increased fracture callus size following osteotomy in mice lacking myostatin (Kellum et al, 2009), and increased fracture callus bone volume in mice treated with myostatin propeptide following osteotomy (Hamrick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%